An examination of the association between history of trauma and schizophrenia symptoms - Sharlene D. Newman; Madeleine Rein; Emily C. Gann; D. Nichole Pompey; Yanyu Xiong (Acta Psychologica, 2025)
Background: Exposure to trauma is associated with increased risk of psychosis. Recent studies investigating the association between trauma history and specific symptoms have reported discrepant findings. Because trauma is suggested to differentially affect females and males, sex differences may contribute to these discrepant findings. Objectives: The current study examined the association between trauma history and experiences of delusions and hallucinations in schizophrenia patients. Additionally, we examined whether sex moderates said associations. Participants and settings: Data from the medical records of 193 psychosis patients from a community behavioral health center were examined. Methods: We investigated the relationships between trauma, hallucinations, and delusions and their dependence on sex utilizing a series of logistic regression models reporting the Wald Chi-square test statistic, p value, and odds ratios. Results: Patients with a trauma history had significantly higher odds of hallucinations (Chi-square: 7.05, p = 0.0079). The odds of reporting hallucinations were 3.46 times higher for individuals with a trauma history. There was no significant association between trauma and delusions. However, sex interacted with the association between trauma and delusions (Chi-square: 4.42, p = 0.0355) - females with trauma history had 0.14 times reduced odds of delusions compared to those who did not report trauma [95 % CI: (0.015, 1.357)] while males with a trauma history had 1.97 times increased odds of delusions. Sex did not interact with the association between trauma and hallucinations. Conclusions: The differing effects of trauma and sex on hallucinations and delusions support the hypothesis that they have different underlying mechanisms.